1999
DOI: 10.1046/j.1420-9101.2000.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the laboratory environment in Drosophila subobscura

Abstract: Adaptation to a novel environment is expected to have a number of features. Among these is a temporal increase in fitness and some or all of its components. It is also expected that additive genetic variances for these fitness characters will fall. Finally, it is expected that at least some additive genetic correlations will decrease, from positive toward negative values. In a study of several life‐history variables in a Drosophila subobscura population sampled from the wild and then cultured in the laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 78 publications
4
91
1
1
Order By: Relevance
“…However, one limitation of the current study may be that colonies were kept under lab conditions for multiple generations before running experiments. Studies have shown that over many generations, some Drosophila species may adapt to laboratory conditions (Matos et al 2000) and values of life history traits may diverge from newly sampled wild populations. However, others have observed similar results for this species.…”
Section: Discussionmentioning
confidence: 99%
“…However, one limitation of the current study may be that colonies were kept under lab conditions for multiple generations before running experiments. Studies have shown that over many generations, some Drosophila species may adapt to laboratory conditions (Matos et al 2000) and values of life history traits may diverge from newly sampled wild populations. However, others have observed similar results for this species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was no evidence for inbreeding effects in the transect lines that had been held in the laboratory for 10 generations. Finally, correlation patterns in the isofemale strains may have been obscured during adaptation to novel environmental conditions (Matos et al 2000) and patterns may have changed as isofemale strains adapt to laboratory conditions. It is difficult to avoid this problem, although the rankings of isofemale strains for a particular trait generally did not change much across generations.…”
Section: Trait Correlationsmentioning
confidence: 99%
“…These components have been extensively reported in the literature for several organisms. In Drosophila, the adaptation to novel environments involving high-density conditions has been studied (Mueller et al, 1993), as well as senescence (Rose, 1984), starvation (Rose et al, 1992), temperature (Huey et al, 1991), fecundity, longevity and developmental time (Matos et al, 2000), and population divergence (Kennington et al, 2001) among others.…”
Section: Introductionmentioning
confidence: 99%